Increased Paediatric Screen Time During Pandemic: A Cause of Concern to Child Health - Yogita Shrivas1, Sujata Shamkuwar2, Radha Andhare2, Ashish Varma3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
COVID-19 has put the globe in an unforeseen and unexpected situation. COVID-19 has affected everydaylife all over the world. Human population came face to face to this virus so gravely for the first time.During the initial days nearly all countries imposed lockdown to break the chain of viral spread. This createdsignificant knock-on effects on the daily life of citizens. With the updates on COVID-19, the guidelinesissued by medical authorities, categorized geriatric and paediatric age groups to be at high risk. In order toflatten the rising curve of exponential spread of the virus ban on gatherings resulted in enforced shut downof schools. Therefore children were bound to stay home. They were automatically exposed to the over useof electronic gadgets for recreation as well as education purpose .Hence, their screen time increased manyfold. This paper describes the impact of COVID-19 and use of electronic screen on children.